PENANGANAN ANAK KESULITAN BELAJAR DISLEKSIA MELALUI PERMAINAN BOWLING KEBERANIAN - Eka Sri Safarina; Hani Susanti (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Handling Children Difficulties Learning Dyslexia through Bowling Game Courage aims to find out what is the difficulty of learning dyslexia, its causal factors, its type and characteristics, even to the way to overcome them. The method used in this research using qualitative methods. Children with special needs that vary such as Autism, mental illness, paralyzed, until the children who have trouble learning difficulties are also included in learners who have privileges. A special child is a child who has a weakness in physical function and cognitive to develop well. The cause varies from the disturbance during pregnancy, interruption at the time of childbirth, to the violence in children, it can cause disruption to the learning of children. This weakness is a weakness that can’t be seen with the eyes like wrong at the time of counting, reading and writing. Therefore there is one way to make learners who get problems with learning, especially reading can be helped with the game of letters and numbers, so that children do not feel bored and quickly memorized with interesting games such as bowling games with courage in addition to children can know the letters and numbers, children can also move by following the motion attached to the bowling pin, the child can also count the number of bowling pins that fall, mention the color of the falling pin, then the results of research that has been done from 3 learners who have problems in reading show good results with already able to mention 3 letters. Keywords: Learning Difficulties, Dyslexia, Courage game of courage.